2013
DOI: 10.1159/000354837
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Platelet Transfusion in Dengue Fever: A Randomized Controlled Trial

Abstract: Background: Scientific data regarding effects of platelet transfusion on platelet count in dengue-related thrombocytopenia is scanty. Methods: A single center, randomized non-blinded trial was conducted on adult patients with dengue fever and platelet counts less than 30,000/μl. Patients were randomized to treatment and control group. Treatment group received single donor platelets. Patients with post-transfusion platelet increment (PPI) ≥10,000/μl and/or corrected count increment (CCI) ≥5,000/μl 1 h post-tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 13 publications
2
40
0
Order By: Relevance
“…A large observational study of critically ill patients showed that 9% (169/1923) of all critically ill patients received platelet transfusions and 55% (296/534 units) of these were given on days when no significant bleeding occurred (Stanworth et al , ). The optimal platelet transfusion management of these patients (Lieberman et al , ) may differ depending upon the underlying clinical diagnosis (Assir et al , ).…”
Section: Prophylactic Transfusion Of Platelets To Other Patient Groupsmentioning
confidence: 99%
“…A large observational study of critically ill patients showed that 9% (169/1923) of all critically ill patients received platelet transfusions and 55% (296/534 units) of these were given on days when no significant bleeding occurred (Stanworth et al , ). The optimal platelet transfusion management of these patients (Lieberman et al , ) may differ depending upon the underlying clinical diagnosis (Assir et al , ).…”
Section: Prophylactic Transfusion Of Platelets To Other Patient Groupsmentioning
confidence: 99%
“…1 So, multiple platelet transfusions, irrespective of appropriate indications can put the patient in serious transfusion-induced complications such as febrile non-haemolytic transfusion reactions, bacterial sepsis, transfusion-related acute lung injury, allergic reactions, alloimmunization, and platelet refractoriness, pulmonary oedema and transfusion transmitted infections. 7,15 Khan Assir et al also revealed that Platelet transfusion despite increasing platelet count in half the recipients neither stopped the progression to severe bleeding nor shortened the time to cessation of bleeding. This proves that a high baseline platelet count and a successful platelet transfusion cannot prevent progression to severe bleeding.…”
Section: Resultsmentioning
confidence: 99%
“…This proves that a high baseline platelet count and a successful platelet transfusion cannot prevent progression to severe bleeding. 15 Blood transfusion services constantly face challenges year after year during dengue outbreaks due to lack of evidencebased guidelines for clinical use of blood and blood components. The demand for platelets and Fresh frozen plasma is increasing due to more number of cases with dengue haemorrhagic fever and dengue shock syndrome.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that there is a correlation between the bleeding degree and the platelet count 13., 14., 15.. The prevention of bleeding in DHF should be directed to the early recognition of shock and immediate correction with PC of and/or fresh frozen plasma (FFP) transfusions 13., 16., 17..…”
mentioning
confidence: 99%
“…Several studies have shown that there is a correlation between the bleeding degree and the platelet count 13., 14., 15.. The prevention of bleeding in DHF should be directed to the early recognition of shock and immediate correction with PC of and/or fresh frozen plasma (FFP) transfusions 13., 16., 17.. The monitoring of hematocrit in series, which reflects the degree of plasma leakage, at the expense of monitoring thrombocytopenia and coagulopathies results in a reduction in the use of blood products 17 .…”
mentioning
confidence: 99%